Characterization and Chromosomal Mapping of Antimicrobial Resistance Genes in Salmonella enterica Serotype Typhimurium - Daly, M. (American Society for Microbiology, 2000)
Two hundred and twenty-six Salmonella enterica serotype Typhimurium isolates were examined for the presence of integron-associated gene cassettes. All but two of the non-DT104 isolates, together with DT104 isolates, contained gene cassettes. Amplicons of 1.5 kbp each were found in two non-DT104 isolates, encoding a dhfrI gene (trimethoprim resistance) linked to an aadA gene (streptomycin and spectinomycin resistance), by site-specific recombination. DT104 isolates of resistance (R) type ACSSuT possessed the recently described 1.0- and 1.2-kbp gene cassettes. Macrorestriction analysis with XbaI and DNA probing mapped ant(3")-1a, bla(PSE-1), and dhfrI genes to large multiresistant gene clusters in a DT170a isolate and a DT193 isolate. In contrast, all DT104 isolates (R-type ACSSuT) possessed a conserved 10-kbp Xba1 DNA fragment. Our study highlights the occurrence of integrons (and antimicrobial resistance determinants) among serotype Typhimurium isolates other than DT104. Larger and previously unrecognized multiresistance gene clusters were identified in these isolates by DNA probing.